Evaluating the link between human resource management decisions and patient satisfaction with quality of care. Issue 1 (January 2017) - Oppel, Eva-Maria; Winter, Vera; Schreyögg, Jonas
Abstract : Background: Patient satisfaction with quality of care is becoming increasingly important in the competitive hospital market. Simultaneously, the growing shortage of clinical staff poses a considerable challenge to ensuring a high quality of care. In this context, a question emerges regarding whether and how human resource management (HRM) might serve as a means to reduce staff shortage problems and to increase patient satisfaction. Although considerable efforts have been devoted to understanding the concepts of patient satisfaction and HRM, little is known about the interrelationships between these concepts or about the link between staff shortage problems and patients' satisfaction with quality of care. Purpose: The aim of this study was to investigate the relationship between strategic human resource management (SHRM), staff shortage problems, and patients' satisfaction with care. Furthermore, we analyze how the HRM decision to fill short-term vacancies through temporary staffing affects patient satisfaction. We differentiate between physicians and nurses. Methodology: We develop and empirically test a theoretical model. The data ( n = 165) are derived from a survey on SHRM that was sent to 732 German hospitals and from a survey on patient satisfaction that comprises 436, 848 patient satisfaction ratings. We use a structural equation modeling approach to test the model. Findings: The results indicate that SHRM significantly reduces staff shortage problems for both occupational groups. Having fewer physician shortage problems is significantly associated with higher levels of patient satisfaction, whereas this effect is not significant for nurses. Furthermore, the use of temporary staffing considerably reduces patients' satisfaction with care. Practice Implications: Hospital managers are advised to consider the effects of HRM decisions on patients' satisfaction with care. In particular, investments in SHRM targeted at physicians have significantly positive effects on patient satisfaction, whereas the temporary staffing of physicians and nurses should be avoided.